Fifth Grade Students’ Learning Styles Based On Differentiated Learning in Elementary Schools - Nurjannah, Ragil Ayu Marta; Ni Wayan Surya Mahayanti; Luh Gd Rahayu Budiarta (Jurnal Pendidikan Bahasa Inggris undiksha, 2024)
The emancipated curriculum emphasizes different learning opportunities tailored to integrate learning styles to meet students' comfort and learning needs. This study aims to analyze the learning styles of 5th-grade in elementary school students in Buleleng so that teachers can implement learning by paying attention to learning styles. This study used a qualitative description approach, with the research subjects being 49 students of 5th-grade from two elementary schools. Data collection used a paper-based questionnaire with learning styles dimension that had been tested for validity. After the data was collected, the data reduction process was carried out by abstracting and categorizing based on learning styles, and the last conclusion-drawing process was carried out. The result of this study is the most dominant visual learning style with 253 responses, kinaesthetic learning style with 251 responses, auditory learning style with 222 responses, and read-write with 214 responses. This proposed research to explore the learning styles of grade 5 students in primary schools, particularly in Buleleng is timely and necessary. It addresses a significant gap in existing research and has the potential to make a substantial contribution to practice, and educational equity in the region.